Comparing traffic classifiers - Gringoli, Francesco; Salgarelli, Luca; Karagiannis, Thomas (Computer Communication Review, 2007)
Many reputable research groups have published several interesting papers on traffic classification, proposing mechanisms of different nature. However, it is our opinion that this community should now find an objective and scientific way of comparing results coming out of different groups. We see at least two hurdles before this can happen. A major issue is that we need to find ways to share full-payload data sets, or, if that does not prove to be feasible, at least anonymized traces with complete application layer meta-data. A relatively minor issue refers to finding an agreement on which metric should be used to evaluate the performance of the classifiers. In this note we argue that these are two important issues that the community should address, and sketch a few solutions to foster the discussion on these topics.